Influence of Extract Swiftlet Nest (Collocalia Fuciphago) as Antihyperglycemia to Circulating Endothelial Cells in Rat (Rattus novergicus) Induced by Streptozotocin - Alexandra, Francisca Diana; M, Satriyandi; Frethernety, Agnes; Triawanti, Triawanti (Berkala Kedokteran, 2018)
Abstract: Hyperglycemia could increase the oxidative stress by catalyzes the formation of free radical as anion superoxide(O2-). Oxidative stress will effect in endothelial damaged. This study aimed to evaluated the influence ofÂ  extract swiftlet nestÂ  (Collocalia fuciphago) to glucose level andÂ  CEC in rat (Rattus novergicus). Rats were classified into 4 groups, there were control group (K) and 3 treatments group (dose 1; 10 and 100 mg / kgBW) The seventh dayÂ  after induced by Streptozotozin (i.p),Â  the ratsÂ  had increasedÂ  glucose Â± 102 â 108 mg/dL, then treatedÂ  with theÂ  extract ofÂ  Â SwiftletÂ  nest for 28Â  daysÂ  byÂ  oral.Â  The CEC was measured by Hladovec method. The results showedÂ  the blood glucose level were significant differences ( p = 0.035). The number of CEC decrease significantly (p=0,002). InÂ  conclusion Â that extract of SwiftletÂ  nest Â can effectÂ  to decreaseÂ  glucose level and CEC number in plasma rat (Rattus novergicus)Â Keywords: Hyperglycemia, Circulating Endothelial Cells, Collocalia fuciphago